Gendered analysis of care work burden and mental health using data from the Gutenberg Covid-19 study - E. Engwicht; J. Petersen; E. Braehler; F. Wicke; J. Koenig; T. Muenzel; A. K. Schuster; K. Lackner; P. S. Wild; M. E. Beutel; Nora Hettich-Damm (Scientific Reports)
Abstract In light of the growing awareness of the unequal distribution of care work, this study aimed to analyze gender differences in burdens of care work and associations with mental health during the COVID-19 pandemic, with a focus on employment status. Therefore, data from the population-representative Gutenberg COVID-19 cohort, collected between October 2020 and April 2021, in the city of Mainz and the County of Mainz-Bingen, Germany, were used. Out of the whole cohort, people living with children in the household were included (N = 2,043). Feeling burdened by care work and mental health outcomes were assessed by validated self-report questionnaires. Descriptive analyses and multilinear regression analyses were performed. Results showed that feeling burdened by care work was more likely for women than for men. For men, feeling burdened by care work was significantly associated with depressiveness, anxiety, and somatization. For women, difficulties with child raising were associated with depressiveness. Part-time working men and women did not differ with respect to mental health or care work burden, whereas unemployed and full-time working women showed significantly worse mental health and reported more burden of care than unemployed and full-time working men. Hence, this study showed gender inequalities. For women, worsening external conditions for childcare appeared to be a risk factor. Men with care work responsibilities seem to benefit, concerning their mental health, from full-time paid work. The data underscore the importance of mitigating the burden of care work, especially to improve conditions for women and part-time workers.